1995
DOI: 10.1016/0370-2693(95)00191-m
|View full text |Cite
|
Sign up to set email alerts
|

The continuum limit of the Schwinger-Dyson equations of the one and two matrix model with finite loop length

Abstract: We take the continuum limit of the Schwinger-Dyson equations of the one and two matrix model without expanding them in the length of the loop. The resulting equations agree with those proposed for string field theory in the temporal gauge. We find that the loop operators are required to mix in the two matrix model case and determine the non-constant tadpole terms. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…[9] Such terms contain the procuct of delta functions δ(l j ) and their derivatives multiplied by a functional of the source functions J n . [20] It is rather difficult to determine those terms solely by integrability conditions and we will not pursue this problem here.…”
Section: A Loop With Vanishing Length Disappearsmentioning
confidence: 99%
“…[9] Such terms contain the procuct of delta functions δ(l j ) and their derivatives multiplied by a functional of the source functions J n . [20] It is rather difficult to determine those terms solely by integrability conditions and we will not pursue this problem here.…”
Section: A Loop With Vanishing Length Disappearsmentioning
confidence: 99%
“…In [4] it was in addition shown that there was universality: the details of the random graphs used in the dynamical triangulation were not important. The concept of a string field Hamiltonian in the case of (p, q) conformal matter coupled to twodimensional quantum gravity was further developed in a series of papers [5,6,7,8]. One outcome was that in the case of (p, q) = (m, m + 1) conformal theories, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of pure gravity, where a complete transfer matrix formalism exists, one finds Hausdorff dimension 4. Recently a string field theory describing the c < 1 m-th minimal model coupled to gravity has been formulated [6,12,13,14,15]. This formulation, combined with the assumption of "classical" area scaling A ∼ l 2 , leads to a prediction d H = 2m.…”
Section: Introductionmentioning
confidence: 99%